Effect of sire and herd interaction on milk production in Sahiwal cattle - KUMAR, AMIT; GANDHI, R S (The Indian Journal of Animal Sciences, 2011)
First lactation records (903) of Sahiwal cows, sired by 46 sires of same breed maintained at 3 different farms were analyzed using sire model of best linear unbiased predictions (BLUP) and 2 different animal models based on derivative free restricted maximum likelihood (DFREML) algorithm. The animal model with sire × herd (S × H) interaction as additional random effect was found to be the best in terms of efficiency and accuracy over other two models. The animal model with interaction explained 15.2% of total phenotypic variation of milk yield due to sire × herd interaction and the estimate of heritability for milk yield was highest (0.182). The herd specific breeding values of sires estimated from interaction model ranged from –441.60 kg to 401.39 kg. The genetic slippage was noticed in most of the sires due to differences in managemental practices followed at different farms. The Karnal herd had highest breeding worth whereas lowest breeding worth was for Lucknow herd. The pooled breeding value over herds showed a declining trend over periods.